Prevalence of Dog Erythrocyte Antigens 1, 4, and 7 in Podenco Ibicenco (Ibizan Hounds) from Ibiza Island. (29th February 2016) - Spada, Eva; Proverbio, Daniela; Viñals Flórez, Luis Miguel; Serra Gómez de la Serna, Blanca; del Rosario Perlado Chamizo, Maria; Baggiani, Luciana; Perego, Roberta
Abstract : The aims of this study were to evaluate the prevalence of Dog Erythrocyte Antigens (DEA) 1, 4, and 7 in Ibizan hounds, to compare the results with the prevalence of DEA in Spanish greyhounds, and to determine the risk of sensitization following the first transfusion of blood not typed for DEA 1 and the probability of an acute hemolytic reaction following a second incompatible transfusion using untyped DEA 1 blood. DEA 1, 4, and 7 status was determined in 92 Ibizan hounds. Results were compared with the previously reported prevalence in Spanish greyhounds. The risks of sensitization and of a hemolytic transfusion reaction were determined amongst Ibizan hounds and between Ibizan hounds and Spanish greyhounds. The prevalence of DEA 1, 4, and 7 was 75%, 98.9%, and 25%, respectively. There was a significantly higher expression of DEA 1 and 7 in Ibizan hounds than in Spanish greyhounds. The probability of sensitization of a recipient dog to DEA 1 with transfusions amongst Ibizan hounds was 18.5% and between Ibizan hounds and Spanish greyhounds was 13.7%. The probability of an acute hemolytic reaction in each group was 3.5% and 1.9%, respectively. There is a higher prevalence of DEA 1 and 7 in Ibizan hounds than in other sighthounds.